Strategi Kesantunan dan Realisasi Tindak Tutur dalam Interaksi Sosial Masyarakat Bugis : Kajian Sosiopragmatik - A. Muh. Taufiq; Muh. Adnan Amar; Sukarni Sukarni (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Language serves not only as a means of communication, but also as a social tool that regulates human relations in a society. In the Bugis society, the practice of language is greatly influenced by cultural values and social norms that govern politeness and communication ethics. This study aims to describe the strategy of politeness and the realization of speech actions in the social interaction of the Bugis community through a sociopragmatic approach. This study uses a qualitative descriptive method with data collection techniques in the form of participatory observation, in-depth interviews, and speech recording in various social contexts. Data analysis was carried out by considering the context of the speech situation, the intention of the speaker, social relations, and Bugis cultural values such as sipakatau, sipakainge, and sipakalebbi. The results of the study show that the indirect politeness strategy is more dominantly used, especially in directive and expressive speech acts. The realization of speech acts is influenced by age, social status, kinship relationships, and communication situations. These findings confirm that language politeness in the Bugis community functions as a social mechanism to maintain harmony, dignity of speakers, and the continuity of cultural values that are closely related to the concept of siri'.